Mesterséges pneumatikus izomelemek modellezése és paramétereinek szimulációja MATLAB környezetben - Sárosi, József; Gyeviki, János; Csikós, Sándor (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
Pneumatic artificial muscles (PAMs) are becoming more commonly used as actuators in modern robotics. The most made and common type of these artificial muscles in use is the McKibben artificial muscle that was developed in 1950's. The braided muscle is composed of gas-tight elastic bladder, surrounded by braided sleeves. Typical materials used for the membrane constructions are latex and silicone rubber, while nylon is normally used in the fibres. This paper presents the geometric model of PAM and different MATLAB models for pneumatic artificial muscles. The aim of our models is to relate the pressure and length of the pneumatic artificial muscles to the force it exerts along its entire exists.